Appraisals, Burnout and Outcomes in Informal Caregiving - Haejung Lee, PhD, RN; Jagdip Singh, PhD (Elsevier, 2010)
This study draws from the resource depletion and conservation theories to develop a process model of informal caregiving. The model includes the burnout as a key mediator of the relationship between benefit/threat appraisals and critical outcomes including perceived physical health, depression and life satisfaction. Methods: A self-report questionnaire was utilized to collect relevant data from 137 informal caregivers of older adults. The proposed model and hypotheses were evaluated with the Structural Equation Modeling method using the software EQS. Results: The relatively high reported levels of emotional exhaustion and reduced personal accomplishment established the relevance of the burnout construct for informal caregivers. In addition, the test of the proposed model provides support for the hypothesis that burnout is an important mediator in the appraisal process model of informal caregiving. However, while burnout effectively mediates the influence of threat appraisals, its role in mediating the effect of benefit appraisals is mixed. Conclusion: The proposed model and results highlight the significance and potential for utilizing a process approach for understanding the link between appraisals and outcomes for informal caregivers. More importantly, the proposed model suggests that attention must be paid toward burnout tendencies to reveal fruitful intervention directions for researchers and practitioners to enhance the positive outcomes of informal caregivers, and maintain their psychological and physical well-being.